(untitled) (SMART MOVES JOURNAL IJOSCIENCE, 2018)
The Cascaded H-Bridge (CHB) multilevel static synchronous compensator (STATCOM) has been widely accepted in the industry [1]-[8]. An outstanding advantage of the CHB multilevel topology is their modular structure. This enables higher-level STATCOM to be easily implemented through series connection of more cells. since the pulse-width modulation (PWM) signals of each cell are generated all by the central controller instead of their own controller, the cell does not look like an “independent module”. To achieve “true” modular implementation, a distributed control system (DCS) for the CHB multilevel STATCOM should be developed.